Instituto Tecnología de Alimentos - Memoria 2024 - Instituto Nacional de Tecnología Agropecuaria (INTA). Instituto Tecnología de Alimentos (Instituto Tecnología de Alimentos, INTA, 2025)
The Food Technology Institute (ITA) aims to generate knowledge, develop and transfer innovative technologies, train and improve human talent and provide strategic services in response to the needs and opportunities of the Argentine Agricultural, Agri-food, Agro-industrial and Bio-industrial System (SAAAB) and future trends. All of this considering aspects related to food safety, nutrition, physical and sensory properties, emerging technologies (nano, bio, ICTs, omics, new processing technologies) and technologies for the use of waste, residues and by-products. This report reports on the activities corresponding to Research and Development, Transfer and Extension, Technological Linkage, Institutional Relations, Institutional Management and Dissemination/Communication corresponding to ITA in the year 2024.